Analisis Faktor Penentu Keberhasilan Pengembangan Produk Baru Liquid Organic Biofertilizer di PT XYZ - Afra Nazhirah; Nabilla Shafira; Azzahra Putri Rialdi; Siti Arita Novia; Nindya Wulandari (Studi Ilmu Manajemen dan Organisasi, 2025)
Purpose: The increasingly competitive fertilizer industry requires companies to pursue continuous product innovation. This study aims to evaluate the influence of product characteristics, sales promotion, and corporate reputation on the success of new product development (NPD) for Liquid Organic Biofertilizer (LOB) at PT XYZ. Methodology/approach: This study employed a quantitative approach using quota sampling involving 48 respondents who are consumers of the LOB product. Data were collected via questionnaires and analyzed using multiple linear regression analysis. Results/findings: The findings indicate that, simultaneously, product characteristics, sales promotion, and corporate reputation significantly affect NPD success. However, partially, only product characteristics have a positive and significant influence. Sales promotion and corporate reputation do not significantly impact NPD success. Limitations: The study's limitation lies in the sample size, which only includes 48 respondents and focuses on one company and one product type, limiting generalizability. Contribution: This study contributes to marketing and product development disciplines by highlighting the dominant role of product characteristics in NPD success in agribusiness. It offers strategic insights for business managers, especially in sustainable agriculture and organic product development.